Awareness about Whole Slide Imaging and Digital Pathology among Pathologists - Cross Sectional Survey - Sandhya Sundar1, Pratibha Ramani2, Herald J Sherlin3, Gheena Ranjith3, Abilasha Ramasubramani4, Gifr (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: To assess awareness of pathologists on whole slide imaging and digital pathology Method: An online, structured questionnaire was sent to pathologists of various dental and medical colleges in Chennai. The data was collected using Microsoft excel version 2011 and statistically analyzed using SPSS software. Results: 28.6% of pathologists were only aware of the fact that whole slide imaging can perform a live scanning of digital images. 81% said the magnification produced by WSI were greater than conventional microscopy. 52.4% agreed on the time taken to perform the whole slide scanning to be one minute. 85.7% were convinced that diagnostic difficulties could be best consulted through the digital slides. 52.4% agreed integrated automated image analysis increased the diagnostic efficacy of WSI in routine histopathology. 62.5% of them felt that the high cost of the equipment and infrastructure was the major impeding factor in usage o f WSI. Conclusion: Whole slide imaging and digital pathology is a promising future of pathology as it can significantly reduce the workload and enhance the diagnostic efficiency in various aspects. There was a reasonable awareness among the pathologists. Until hospitals collaborate and take initiative to bring whole slide imaging into practice, its difficult to make the best of its advantages.